Body Composition and Physical Fitness Tests Among US Army Soldiers: A Comparison of the Active and Reserve Components. (September 2019) - Russell, Dale W.; Kazman, Joshua; Russell, Cristel Antonia
Objectives: US Army reserve soldiers and active-duty soldiers differ in their daily work demands and supporting resources, yet research on reservists' health and fitness is lacking. The objectives of this study were to (1) determine whether physical test failure rates and health behaviors differed between active-duty soldiers and reserve soldiers and (2) establish which demographic and health behavioral factors were associated with failing physical tests. Methods: We analyzed a sample of 239 329 US Army active-duty and reserve soldiers surveyed from September 2013 through March 2015 using the Global Assessment Tool. We extracted data on soldier demographic characteristics and health behaviors, as well as Body Composition Test (BCT) and Army Physical Fitness Test (APFT) results. We compared the 2 groups using the active-to-reserve adjusted odds ratio (aOR) for each variable. We used logistic regression models to determine which variables were associated with failing these tests. Results: The odds of failing the BCT (aOR = 0.76; 95% confidence interval [CI], 0.73-0.78) or the APFT (aOR = 0.31; 95% CI, 0.30-0.32) were lower among active-duty soldiers than among reservists, and the odds of doing high levels of high-intensity interval training (aOR = 1.47; 95% CI, 1.42-1.51), resistance training (aOR = 1.45; 95% CI, 1.42-1.48), and vigorous physical activity (aOR = 2.92; 95% CI, 2.86-2.98) were higher among active-duty soldiers than among reservists. The odds of using tobacco (aOR = 1.37; 95% CI, 1.35-1.40), binge drinking alcohol (aOR = 1.11; 95% CI, 1.09-1.13), having insomnia (aOR = 1.46; 95% CI, 1.43-1.48) or mild depression (aOR = 1.50; 95% CI, 1.48-1.53), and sustaining a physical activity–related injury (aOR = 2.52; 95% CI, 2.47-2.57) were higher among active-duty soldiers than among reservists. Conclusions: Policy makers and military leaders could use this information to implement health screenings and tailor health-promotion, intervention, and treatment programs.